Reflective Journal on Pre-Service English Teachers’ Practicum Teaching - Fitria, Wahyuni; Faizah, Nurul; Saijun, Saijun (UNIB Press, 2024)
Reflective practice is illustrated in how instructional strategies are organized, developed, implemented, and evaluated by pre-service teachers, while assessments are utilized to offer feedback to educators, supporting the maintenance or enhancement of their pedagogical methods. By participating in reflective practices, pre-service teachers' understanding and appreciation of the inherent value and passion of teaching can be deepened, which subsequently becomes visible in their professional behavior. This study examined the perceptions of pre-service English teachers regarding their experiences with reflective journaling during their teaching practicum. A qualitative approach was employed, utilizing a case study design, with data collected from ten pre-service English teachers at an Islamic public university in Jambi, consisting of eight female and two male students. Data were gathered through interviews and analyzed using an open coding method. The findings suggest that pre-service teachers primarily reflected on their classroom teaching abilities, particularly focusing on the technical aspects of teaching practice. Moreover, the SWIS (Strengths, Weaknesses, and Suggestions for Improvement in Teaching) framework was identified as a key advantage of journal reflection.